Accuracy and precision of transcutaneous carbon dioxide monitoring: a systematic review and meta-analysis. Issue 2 (12th September 2018) - Conway, Aaron; Tipton, Elizabeth; Liu, Wei-Hong; Conway, Zachary; Soalheira, Kathleen; Sutherland, Joanna; Fingleton, James
Abstract : Background: Transcutaneous carbon dioxide (TcCO2 ) monitoring is a non-invasive alternative to arterial blood sampling. The aim of this review was to determine the accuracy and precision of TcCO2 measurements. Methods: Medline and EMBASE (2000–2016) were searched for studies that reported on a measurement of PaCO2 that coincided with a measurement of TcCO2 . Study selection and quality assessment (using the revised Quality Assessment of Diagnostic Accuracy Studies tool (QUADAS-2)) were performed independently. The Grading Quality of Evidence and Strength of Recommendation approach was used to summarise the strength of the body of evidence. Pooled estimates of the mean bias between TcCO2 and PaCO2 and limits of agreement with outer 95% CIs (termed population limits of agreement) were calculated. Results: The mean bias was −0.1 mm Hg and the population limits of agreement were −15 to 15 mm Hg for 7021 paired measurements taken from 2817 participants in 73 studies, which was outside of the clinically acceptable range (7.5 mm Hg). The lowest PaCO2 reported in the studies was 18 mm Hg and the highest was 103 mm Hg. The major sources of inconsistency were sensor location and temperature. The population limits of agreement were within the clinically acceptable range across 3974 paired measurements from 1786 participants in 44 studies that applied the sensor to the earlobe using the TOSCA and Sentec devices (−6 to 6 mm Hg). Conclusion: There are substantial differences between TcCO2 and PaCO2 depending on the context in which this technology is used. TcCO2 sensors should preferentially be applied to the earlobe and users should consider setting the temperature of the sensor higher than 42°C when monitoring at other sites. Systematic review registration number: PROSPERO; CRD42017057450.